2020
DOI: 10.3390/antibiotics9060316
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Tool for the Presence of Ceftriaxone-Resistant Uropathogens upon Hospital Admission

Abstract: Antimicrobial resistance among uropathogens is a particularly pressing problem in the Asia-Pacific region. The objectives of this study were to determine the incidence and susceptibility of uropathogens upon hospital admission and to develop a risk-scoring model to predict the presence of ceftriaxone-resistance uropathogens (CrP). This was a retrospective observational cohort study of patients with a positive urine culture within 48 h of presentation at National University Hospital, Singapore between June 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The Singapore study reported that co-amoxiclav was the second most prescribed antibiotic for UTIs, followed by piperacillin tazobactam and ciprofloxacin [22]. These differences may be attributed to variations in antimicrobial resistance patterns between the two countries and differences in clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The Singapore study reported that co-amoxiclav was the second most prescribed antibiotic for UTIs, followed by piperacillin tazobactam and ciprofloxacin [22]. These differences may be attributed to variations in antimicrobial resistance patterns between the two countries and differences in clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of BRIAT increased from 13.0% to 69% as the number of risk factors increased from 0 to 4. The absence of risk factors, however, cannot rule out ESBL positivity and reported models to predict antibiotic susceptibility for urinary tract infections to third-generation cephalosporins such as ceftriaxone are poor with c-statistics <0.70 [ 7 , 79 ]. Mark et al [ 40 ] reported ESBL infection risk factors in 82–81% of patients admitted with a febrile UTI in those with and without BRIAT.…”
Section: Urine Culturesmentioning
confidence: 99%
“…Ceftriaxone Escherichia coli resistance rates worldwide range from 5% to over 90% with a median of 45% [ 78 , 80 , 81 ]. Reports of ceftriaxone and other third-generation cephalosporins resistance rates vary from 12.9% in Northern California patients admitted with fever and a positive urine culture [ 40 ], 29% [ 79 ] of patients admitted to the hospital in Singapore and up to 43% of Turkish patients with pyelonephritis [ 82 ]. In Mexico [ 83 ] the prevalence of Escherichia coli -resistant organisms was 32.1%, and the average resistance rate for all the Enterobacteriaceae in University hospitals affiliated with the Center for Disease Control research network in the USA was 21% [ 84 ] ranging from around 5% to 45%.…”
Section: Urine Culturesmentioning
confidence: 99%